Efektivitas Implementasi Penggunaan Quick Response Indonesian Standard (QRIS) Pada Usaha Mikro Kecil dan Menengah (UMKM) di Kelurahan Jempong Baru - Samahudin, Samahudin (Fakultas Syariah IAI Hamzanwadi Pancor, Lombok Timur, Indonesia, 2025)
This study was conducted with the aim of determining the implementation of the use of QRIS (Quick Response Indonesian Standard) and the effectiveness of the use of QRIS (Quick Response Indonesian Standard) in MSMEs (Micro, Small and Medium Enterprises) in Jempong Baru Village. The development of technology that continues to grow day by day so that people must be able to adapt quickly to these changes. One of the developments that must be followed by the community is online or non-cash payments. The presence of the QRIS application is one way to facilitate payment transaction activities in business activities. This is what MSMEs in Jempong Baru Village then tried to implement. The method used in this study is to use a descriptive qualitative approach, data collection through interviews, observation and documentation. Data analysis was carried out using a data reduction analysis model, data presentation and conclusions/verification. The results of the study show that the implementation of the use of QRIS (Quick Response Indonesian Standard) in Jempong Baru Village is quite effective, this is because the implementation of non-cash payments is very useful and can be understood by the local community and the cause of many MSMEs in Jempong Baru Village implementing the system is because the transaction process is very effective, easy, fast and safe.